Petei and Mocoi: two rice cultivars developed through anther culture in Argentine - Marassi, Maria Antonia (2000)
We developed two rice varieties, Petei and Mocoi, through anther culture. These varieties were released in 1997 for commercial cultivation in Argentina. Petei was developed from a cross involving cultivars Quella and Guayquiraro, which were made avaible to the rice program at the Julio Hirschhorm Experimental Station,FCAF. Selected plants from the F population of this cross were used for anther culture the biotechnology laboratory, FCA, UNNE. Mocoi was developed from crossing two F1s (H342 and H161-28-2-2-1). H342´s parents were Guayquiraro and Nucleoryza, whereas H16r28-2-2-1had Calady 40 and lRll03- 15-10 as parents. Anther culture was performed on the F1s and progenies were multiplied for further evaluation.